Theme Analysis in the Film Percy Jackson & the Olympians: The Lightning Thief Based on Greek Mythology - Telaumbanua, Dispensasiani; Tambunan, Mirnawati; Zendrato, Keisha Amanda; Lestari, Nia; Syahputa, Fikry Prastya (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the main themes found in the film Percy Jackson & the Olympians: The Lightning Thief (2010) based on Greek mythology. The film adapts classical mythological stories and presents moral values and conflicts that remain relevant to modern teenage life. This research employs a descriptive qualitative method using thematic analysis to identify the central themes of the film. Data were collected through documentary observation and literature review, then analyzed using the thematic analysis model by Miles, Huberman, & Saldaña. The results of the study reveal four dominant themes in the movie: identity and self-discovery, friendship and loyalty, the conflict of good versus evil, and heroism and sacrifice. These themes represent the moral values of Greek mythology adapted into the context of modern life. The findings are expected to contribute to the study of modern literature and classical mythology adaptation in popular media. Unlike previous studies that focused on character and plot analysis in mythological film adaptations, this research specifically examines the film’s thematic structure and moral messages using a thematic analysis approach by Miles & Huberman. This offers a fresh perspective in understanding how classical mythology is reinterpreted in contemporary popular culture.